Building Capacity for Computational Thinking in Youth through Informal Education. - Mesiti, Leigh Ann; Parkes, Alana; Paneto, Sunewan C.; Cahill, Clara (Journal of Museum Education, 2019)
Building Computational Thinkers, a three-year research study, explored how educators and designers can most effectively support the development of computational thinking capacity, and how these learning experiences could be customized to meet the needs of different learners. This research study focused on three specific exhibit design approaches that conveyed problem decomposition content in The Science Behind Pixar (Pixar), a 13,000 square foot traveling exhibition about the computer science, mathematics, and science behind Pixar's innovative films. Phase One investigated how novice learners could be supported to interact with exhibits and understand problem solving strategies that tackle complex, creative challenges in computer programming. Phase Two investigated the affordances of these exhibits to build capacity, feelings of efficacy, and interest in problem decomposition content in middle and high school youth. The findings in this paper describe the types of scaffolds that can be used to support computational thinking in novice youth, as well as how a combination of exhibit approaches were found to increase youth perceptions, understanding, and beliefs of computer programming. It will also discuss how two exhibit approaches worked particularly well for engaging girls in problem decomposition content.